CONSTRUCTIVE IMPORTANCE OF AETHETIC IDEAL IN FORMING AESTHETIC CONSCIOUSNESS OF THE PERSON - Samadov, Aktamkul Rafikovich (International Journal of Psychosocial Rehabilitation, 2020)
this article is about importance of aesthetic ideal and forming of aesthetic consciousness of the person. Aesthetic attitude of aesthetic person to presence which include aesthetic consciousness and activity of the person is analyzed.